PELAKSANAAN DIVERSI TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM PADA PROSES PENYIDIKAN MENURUT UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK: Qurota Aini - admin, admin; Hariz Hamdallah, Muhammad Andika (Fakultas Hukum Universitas Islam Jakarta, 2018)
Parents, environment, and state apparatus must protect children by protecting them rights as child because in essence child can not protect themself form a crime.One way to protect the rights of a child is by seeking Diverstion through a Restorative approach. Diverstion is the transfer of the settlement of a child case from criminal justice process to a process outside of criminal justice. While Restorative Justice is the settlement of criminal case involving perpetrators, victims, families of perpetrators / victims, and related parties to jointly seek a fair settlement by emphasizing restoration back to the original state not retaliation. Divertion in this undergraduate thesis is at the level of investigation. The implementation of this version of the investigation is not easy, many obstacles occured in the field. The method used in this study is the normative juridical research that emphasizes the use of legal norms in writing and supported by interviews with resource persons and informants. The results of research and analysis can be concluded that Divertion is one way to realize Restorative Justice. Divertion is not run against serious criminal offenders whose criminal threats are above 7 (seven) years. Implementation Divertion experiencing barriers both internally and externally. Divertion with Restorative Justice approach is in line with qishash-diyat principle.